A not-so-novel approach to managing scholarly communication: Applying the principles of records management to the scholarly record - Martín-Martín, Alberto (Anuario ThinkEPI, 2022)
An aspect that in my view is insufficiently questioned in conversations about the future of scholarly communication is the framing of academic documents as products of a publishing industry (publications). Here, I propose that documents that serve as evidence of scholarly and scientific activities should be primarily understood as records (elements of an archive), with all that this entails. This is compatible both with the public nature of many of these documents and with the need for editing processes. The result would be a true scholarly record that is worthy of its name, something that could not exist in the past because of technical limitations. This radical shift in perspective reveals the need for academic institutions and communities to take responsibility for the governance of scholarly communication processes, a demand recently voiced by several international organizations and expert groups. The approach outlined here intends to place the management of processes in scholarly communication at the same level as any other human activity that generates documents that are considered necessary to keep supporting said activity. In other areas, responsible organizations apply the principles of records management to appraise and implement the workflows that best support the activities of the organization. This is not the case in scholarly communication, where owing to historical reasons, communication is structured around an industry in which a small number of commercial actors have eventually amassed a disproportionate amount of power, ultimately giving rise to models in which a number of sectors of the academic community are systematically excluded on economic grounds. In summary, this work argues that the digital transformation of scholarly communication points to the need for scholarly records management. Initiatives such as the FAIR principles can be framed as steps in this direction.
Keywords: Scholarly communication; Scholarly publications; Scholarly publishers; Records management; Scholarly record; Governance; FAIR